ACSM expert consensus statement: Considerations and recommendations for prescribing exercise and designing physical activity programs for people with disabilities - Ptomy, L., Morgan, K. A.; Blauwet, C. A.; Boudreaux, B. D.; Fernhall, B.; Hauck, J.; Legg, D.; Tow, S.; Martin, Ginis, K. A. (Medicine & Science in Sports & Exercise, 2025)
Participating in physical activity and meeting physical activity guidelines are far more challenging for persons with disabilities than for the general population. This American College of Sports Medicine expert consensus statement provides an evidence-based summary of (i) the impact of physiological factors, physical activity guidelines, and barriers on physical activity participation and prescription for individuals with disabilities; (ii) three consensus statements derived from research evidence; and (iii) five practical recommendations for prescribing and designing physical activity programs tailored to adults with disabilities, based on an integration of research evidence with expert consensus.